Keragaman Serangan Hama dan Penampilan Agronomik pada Varietas Kedelai Burangrang dan Anjasmoro - Suprapto, Suprapto; Pujiharti, Yulia (Politeknik Negeri Lampung., 2012)
Study the diversity of insect pests in soybean varieties mentioned by Anjasmoro and Burangrang has been done AIAT on the Experimental Garden Natar, South Lampung in January 2011 to March 2011.The research aims to obtain a high production of soybean varieties and pest tolerant. The study used two varieties of soybean called by Anjasmoro and Burangrang, with an area of 0.5 ha each variety. Observations made on 100 plants were randomly sampled and using sweep nets to insect catcher with 10 swings each observation. Observations on height plant, number of pods per plant, number of healthy pods and pests per plant, number of seeds, damaged seeds and healthy seeds per plant, the weight of healthy, species and number pests damaged seeds per plant and the production of soybeans per acre.Analysis data by t-test at level significant 5% and 1%. Results showed that insect pests on varieties Anjasmoro and Burangrang enough variety, the varieties Anjasmoro found 15 species of 9 families and 6 orders and on Burangrang found 11 species of 7 families and 5 orders. Burangrang varieties have high plant (65.4 cm), number of pods per plant (23.73 pods) and healthy pods 22,0 (92,70%) per plant higher than Anjasmoro varieties have high plant 50.53 cm, number pods 15,13 per plant and healthy pods 12,1 (79,97%) per plant. Number of seed varieties Burangrang 46.43 per plant and seeds of healthy 42.4 (91.32%) per plant higher than that of Anjasmoro which has only 28.6 seeds per plant, seeds healthy 24.23 (84.72%) per rod. Burangrang varieties have seed weight (219.6 g) per plant , weight of healthy seeds (209.2 g) per plant and soybean production (1215.11 kg) per hectare were higher than that of Anjasmoro varieties that only have seed weight 118.6 gr per plant , weight of healthy seeds 112.8 gr and production 802.25 kg per hectare. Keywords: soybean, diversity, pests, Agronomic Performances, production.